Strain Hardening of Nickel-Based Alloys: Microstructure Related Analytical Evaluations, Molecular Dynamics Modelling, and Effects of Ultrasonic Surface Finishing - B.M. Mordyuk, V.М. Shyvaniuk, G.S. Mogylnyi, V.І. Bondarchuk, and О.S. Gatsenko (Успехи физики металлов, 2025)
This paper aims to review and analyse the feasibility of surface finishing of various types for strengthening and improving other properties of aviation nickel-based alloys. The peculiarities of changes in the structural–phase state and mechanical properties of the surface layers of samples of Inconel 690, Inconel 718, and Inconel X750 (CrNi73MoTiAlNb) alloys obtained by the standard technology of casting and thermomechanical processing are considered after heat treatment and subsequent ultrasonic surface finishing using high-frequency mechanical impact (HFMI) treatment. Using scanning electron microscopy and energy dispersive x-ray spectroscopy, both dimensional and morphological features, and the volume fraction of strengthening phases are identified. As shown, the HFMI treatment allows effective strengthening of the surface layers of aviation nickel alloys to increase their operational characteristics. The magnitudes of the compressive stresses in the surface layers formed due to severe plastic deformation during HFMI are of ≈0.71 GPa, ≈0.82 GPa, and ≈1.25 GPa, and hardness HV increases to 3.75 GPa (by 75%), 4 GPa (55%), and 5.96 GPa (41%) for Inconel 690, Inconel 718, and Inconel X750, respectively. The observed hardness increase is described both experimentally by accounting for microstructural data and analytically based on the hardening mechanisms involved, namely: the solid-solution hardening, dispersion hardening by carbides (Inconel 690) and/or intermetallics (Inconel 718, Inconel X750), dislocations’ accumulation and rearrangement, and grains/subgrains refinement observed by x-ray structural analysis. As shown, molecular-dynamics modelling under the same conditions of tensile stress and temperature allows capturing the difference in the evolutions of the defect structures and stress fields averaged on all atoms of the model Ni nanocrystals with and without a spherical inclusion, and it can be used for modelling the alloys with dispersion strengthening. The dislocation bundles around spherical inclusion and intersecting slip bands revealed in the Ni lattice during the molecular-dynamics modelling were also found at another scale level by the direct transmission electron microscopy observations of the microstructure of the ultrasonic impact treatment-deformed Inconel 718.